Insulin resistance and its possible personal stress moderators - Oleg G. Motovilin; Elena V. Surkova; Alexander Y. Mayorov; Ekaterina O. Koksharova; Olga G. Melnikova (Сахарный диабет, 2017)
Background. Recently, insulin resistance (IR) has been actively investigated by experts in various fields. Here we aim to study the effect of stress on the development of IR. Objective. To study the associations between IR and personal stress moderators (self-attitude, locus of control and coping strategies) as well as the related performance lifestyles. Methods. The study included 63 patients (16 men; mean age, 48.2 ± 11.7 years). Of these participants, 26 were diagnosed with type 2 diabetes mellitus, 10 with impaired glucose tolerance, 6 with impaired fasting glucose and 21 with normal glucose tolerance. The levels of HbA1c and IR ratio were determined using HOMA. Well-known psychological assessment questionnaires were used to assess the effect of personal stress moderators. Results. There was a significant relationship between IR and personal stress moderators. A positive self-attitude was associated with a lower risk of IR (p < 0.05), which can be explained by a decrease in the risk of developing stress. Assertive coping strategies were most pronounced in subjects with a low level of IR (p < 0.05). Personal characteristics also determined an individual’s lifestyle, which may have an impact on the increase in IR. There was an association between high levels of IR and unhealthy alimentary preferences (p < 0.05). Such preferences were also associated with personal characteristics, such as external locus of control, less positive self-attitude and passive coping strategies (p < 0.05). People with high IR rarely engage in a regular physical activity; there was a direct correlation between the frequency of physical activity and assertive coping strategies (p < 0.01). Married participants had high levels of IR (p < 0.05). Conclusion. There were significant relationships between IR and personal stress moderators, such as self-attitude and coping strategies. Besides the direct effects on stress levels, personality traits may also indirectly increase the risk of IR by influencing the individual’s lifestyle. There is a need to investigate the fact that married people have higher levels of IR.